Solid Particle Erosion of a Limestone Target Surface under Controlled Conditions - Anna Laura Sanna; Giorgio Pia; Francesco Delogu (Advances in Materials Science and Engineering)
This work focuses on the erodent capability of yttria-stabilized zirconia beads impacting on a limestone target surface. The target surface was used as the cap of a hardened steel vial clamped on a SPEX Mixer/Mill 8000. The vial three-dimensional swing results in repeated bead impacts that cause the material removal from the target surface. The mass loss varies linearly with the number of beads, which allowed estimating the mass lost per bead per impact. It amounts approximately to 70 ng, a value that compares fairly well with the one of about 80 ng estimated from the volume of the indents left on the target surface by individual impacts. Experimental findings indicate that the methodology developed can be reliably utilized to investigate solid particle erosion under highly reproducible and controllable experimental conditions.